Upaya Pustakawan dalam Meningkatkan Minat Baca Anak di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Linda, Andri Agnesa; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
The purposes of this article are to describe: (1) librarian effort to increase the reading interest of children in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat; (2) the problem faced by librarian to increase the reading interest of children in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat. Data were collected by interview wiht the officer of Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat and observation. Based on this research, there are some summary. They are: (1) librarian effort to increase the reading interest of children in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat were, provide facilities and infrastructure, periodically updating collections of books, provide special services for children, cozy room design, cooperation with schools, add librarian that work in children service; (2) the problem faced by librarian to increase the reading interest of children in Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat were, table and chair are limited, children playground is not yet available, lack atention of children to reading, activity room children inadequate, room paint colour does not interesting, lack of librarian on children’s service.Keywords: Kata kunci: Effort, problem, interest, reading